Caribou distribution during calving in the northeast National Petroleum Reserve-Alaska, June 1998 to 2000 - Noel, Lynn E.; George, John C. (Rangifer, 2003)
Barren ground caribou (Rangifer tarandus granti) of the Teshekpuk Caribou Herd (TCH) inhabit the western portion of Alaska's Arctic Coastal Plain within the National Petroleum Reserve—Alaska (NPR-A). Alaska's North Slope communities, management agencies, and private industry are interested in this herd because of its importance as a subsistence resource and location relative to potential petroleum development. From 1998 through 2000, we monitored caribou distribution during the calving period within the Northeast Planning Area of the NPR-A using systematic strip-transect aerial surveys, as well as VHF and satellite telemetry for cow caribou. Aerial survey and telemetry data indicated cows with calves were distributed around Teshekpuk Lake, with a concentration south of the lake in 1999 and 2000. Inconsistencies in weather conditions, survey timing (both strip-transect and VHF surveys), 100% coverage survey areas, and small sample sizes confound interpretations of our results. However, several patterns were apparent. Later transect survey timing (7—12 June versus 4—7 and 5—8 June) resulted in more cow/calf pairs recorded. Our 18% coverage area, originally based on VHF telemetry data for the extent of TCH calving, covered a consistently high proportion (95% to 100%) of the annual calving ranges (95% kernel utilization distributions), but accounted for only 24% to 46% of the adult cows in the TCH based on the current Alaska Department of Fish and Game population estimate (1999) and average 1998¬2000 herd composition. It appears that either our transect survey methodology significantly underestimated the true number of caribou cows in the study area, many cows calved outside the area or moved into the area and calved after our surveys, or we have over estimated the number of reproductive cows in the herd. Our 100% coverage transect areas covering oil and gas lease areas, contained 38% of the calving range with 23% of TCH cows in 1999; and 18% of the calv¬ing range with 8% of TCH cows in 2000. Based on 95% minimum convex polygon ranges, satellite collared cow/calf pairs were not stationary during either our survey period (14.7 ± 6.56 km2; mean ± standard error of the mean; 4—12 June) or during the calving period (86.9 ± 72.30 km2; 1—20 June) during 1998—2000. Site specific pre-development data on caribou distribution during calving in NPR-A will be useful for assessing the importance of specific areas to caribou during calving and for designing oilfields that minimize impacts should oil development occur.